Pharmacist-led intervention to improve medication use in older inpatients using the Drug Burden Index: a study protocol for a before/after intervention with a retrospective control group and multiple case analysis. Issue 2 (20th February 2020) - Dearing, Marci Elizabeth; Bowles, Susan; Isenor, Jennifer; Kits, Olga; Kouladjian O'Donnell, Lisa; Neville, Heather; Hilmer, Sarah; Toombs, Kent; Sirois, Caroline; Hajizadeh, Mohammad; Negus, Aprill; Rockwood, Kenneth; et al.
Abstract : Introduction: Polypharmacy and potentially inappropriate medication use is common in older adults and is associated with adverse outcomes such as falls and hospitalisations. Methods and analysis: This study is a pharmacist-led medication optimisation initiative using an electronic tool (the Drug Burden Index (DBI) Calculator) in four hospital sites in the Canadian province of Nova Scotia. The study aims to enrol 160 participants between the preintervention and intervention groups. The Standard Protocol Items: Recommendations for Interventional Trials (SPIRIT 2013 checklist) was used to develop the protocol for this prospective interventional implementation study. A preintervention retrospective control cohort and a multiple case study analysis will also be used to assess the effect of intervention implementation. Statistical analysis will involve change in DBI scores and assessment of clinical outcomes, such as rehospitalisation and mortality using appropriate statistical tests including t-test, χ 2, analysis of variance and unadjusted and adjusted regression methods. Ethics and dissemination: Ethics approval has been granted by the Nova Scotia Health Authority Research Ethics Board. The findings of this study will be published in peer-reviewed journals and presented at local, national and international conferences. Trial registration number: NCT03698487 .